Integrated resistivity study on the effect of dumpsite leachate on groundwater at Ezeani-Obimo, Nsukka, Enugu state Nigeria - Mirianrita Ngozi Ossai; Benjamin Shaibu Ojoajogwu; John Akor Yakubu (International Journal of Advances in Applied Sciences, 2022)
The effect of dumpsite leachate on groundwater at the Ezeani-Obimo community was performed by employing Schlumberger and Wenner configurations for four vertical electrical sounding (VES) and four electrical resistivity tomography (ERT). Four geoelectric layers were obtained and characterized by KH, AK, KH, and QH curve types. The first layer, second and third layer has resistivity values ranging from 21.2 to 7026.0  with thickness and a depth ranging from 0.5-31.6 m. The fourth layer has resistivity values ranging from 105.9 to 3355.4  with undefined thickness and depth values harboring all the aquifer units in the study area. Aquifer resistivity and thickness values vary from 105.9 to 3355.4  and 6.6 to 27.1 m while aquifer conductivity ranges from 0.0003 to 0.0094  increasing towards the E-W direction. The longitudinal conductance and transverse resistance values vary from 0.0024 to 0.0623  and 698.94 to 27178.7  respectively. 2D ERT profiles show low resistivity in the eastern direction and a lateral spread of low resistivity value indicates that leachate flow is moving away gradually from the dumpsite to its outside environment. This study revealed that the layers harboring the aquifer in the area are significantly affected as a result of dumpsite leachate that accumulates on the surface. This result is beneficial for waste managers to take mitigation measures to prevent the risk of total contamination of the groundwater in the area in the nearest future.